SOURCE OF THE FE-RICHED-TYPE HIGH-MG MAGMA IN MAZHARTAG REGION, XINJIANG - Jiang C.; Lu D.; Bai K.; Jia C.; Li L.; Zhang P. (My University, 2004)
A group of Permain vein rocks, which intrude into the stratum of Sliurian system, Devonian system, Carboniferous system and lower Permain series, occur in Mazhartag region, located in the west margin of the Tarimu plate, eastern Bachu county. Their main rock types have diabases, diabase-prophyrites, chromocratic olivine gabbros and lamprophyres. The chromocratic olivine gabbros, with Fe 2O 3+FeO=14.40%～16 88%, MgO=17 21%～18 59%, Mg#=67～68, FeO t/MgO1 and Ni=469×10 -6～635×10 -6, belong to the Fe-riched-type high-Mg magma and are more or less representative of the primary magma, while Mg#, FeO t/MgO and Ni abundance of the diabases and diabase-prophyrites show these rocks belong to the moderately evolved magma. It is proved by the petrography and petrochemistry that the fractional crystallization of the olivines and clinopyzoxenes is the main mechanism of the magmatic evolution. All varial vein rocks have the characteristics of the rare earth element and trace element geochemical characteristics of basalts formed under the extension settings of the intra-plate. All rocks,with 143Nd/ 144Nd= 0 512508～0 512786, 87Sr/ 86Sr=0 704246～0 706444, 206Pb/ 204Pb= 18 17～19 24, 207Pb/ 204Pb=15 47～15 71 and 208Pb/ 204Pb=38 63～39 32, have the identical Nd, Sr and Pb isotopic compositions. Therefor, it can be proved that these vein rocks have Nd, Sr and Pb isotopic compositions of the primitive mantle and their magmatic source maybe lay in the lower mantle.